1994
DOI: 10.1093/jnci/86.19.1458
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of a Retroviral Wild-Type p53 Expression Vector in an Orthotopic Lung Cancer Model

Abstract: Development of gene-replacement treatment strategies based on the type of mutations found in target cancers is warranted and may lead to the development of new adjunctive therapies and gene-specific prevention strategies for lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(91 citation statements)
references
References 0 publications
2
87
0
2
Order By: Relevance
“…Although mesothelioma presents a disease that may potentially be approached by gene therapy, it seems unlikely that this strategy would be capable of reaching every cancer cell. Re-expression of other tumor suppressor genes have been associated with thè bystander' e ect wherein neighboring tumor cells are killed by mechanisms dependent on their proximity to tumor cells which have been recipients of a suppressing gene vector (Fujiwara et al, 1994). It is possible that such a bystander e ect may play a role in p16 INK4a -mediated tumor suppression, although we have not evaluated this in the current investigation.…”
Section: Discussionmentioning
confidence: 95%
“…Although mesothelioma presents a disease that may potentially be approached by gene therapy, it seems unlikely that this strategy would be capable of reaching every cancer cell. Re-expression of other tumor suppressor genes have been associated with thè bystander' e ect wherein neighboring tumor cells are killed by mechanisms dependent on their proximity to tumor cells which have been recipients of a suppressing gene vector (Fujiwara et al, 1994). It is possible that such a bystander e ect may play a role in p16 INK4a -mediated tumor suppression, although we have not evaluated this in the current investigation.…”
Section: Discussionmentioning
confidence: 95%
“…We and others previously reported that restoring the wt p53 gene by viral or nonviral vectors inhibited the growth of NSCLC cell lines in vitro and in vivo. [7][8][9][10] There is evidence that the apoptotic activity of wt p53 is of central importance for its tumor suppressor activity. 11 However, the relative contribution of cell cycle arrest versus apoptosis in p53-mediated tumor regression has not been extensively documented.…”
Section: Introductionmentioning
confidence: 99%
“…For those cells whose apoptosis may be p53 dependent and at the same time p53 deficiency does exist, it may be advisable to transduce wide type p53 gene into these cells to reendow them with sensitivity to chemotherapy. Experiments showed that p53 transduced vectors can induce the apoptosis of p53 mutated nonsmall-cell lung carcinoma, squamous epithelial carcinoma and transplanted human mammary carcinoma in mude mice and sometime even inhibit their metastasis [25][26][27][28].…”
Section: Apoptosis and Traditional Tumor Therapy (1) Traditional Tumomentioning
confidence: 99%